GAMBARAN SANITASI LINGKUNGAN MASYARAKAT PESISIR PANTAI DI DESA TATELI - Natasya O. R. Runtulalo (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Environmental sanitation is an important factor in public health. Sanitation problems are one of the biggest challenges facing developing countries. According to the World Health Organization (WHO), one child dies from diarrhea every 15 seconds worldwide due to lack of access to sanitation. The purpose of this study was to determine the description of environmental sanitation in coastal communities in Tateli Village. The method used is quantitative research using descriptive methods. The population in this study were all houses in Tateli Village. The sample studied in this study used a total sampling technique where all populations were sampled, namely 48 houses as respondents. Data were collected using a questionnaire, then analyzed univariately. The results show that the description of environmental sanitation of coastal communities in Tateli village is, Healthy housing conditions that do not meet the requirements are more with a percentage of 77.1% compared to those that meet the requirements, Clean water supply conditions that meet the requirements are more with a percentage of 58.3% compared to those that do not meet the requirements, Family toilet conditions that do not meet the requirements are more with a percentage of 83.3% compared to those that meet the requirements, Wastewater drainage channels are more qualified with a percentage of 79.2% compared to those that do not meet the requirements, Waste bin facilities that do not meet the requirements are more with a percentage of 77.1% compared to those that meet the requirements.